2011
DOI: 10.1108/10610421111108021
|View full text |Cite
|
Sign up to set email alerts
|

Umbrella brand price premiums: effects of compatibility, similarity, and portfolio size

Abstract: PurposeThe study aims to examine the characteristics of product portfolio on the price premium of an umbrella brand. Specifically, the study seeks to explore three aspects of a product portfolio: the presence of attribute compatibility, similarity, and portfolio size.Design/methodology/approachA total of 232 subjects participated in the 2 (with/without compatibility)×2 (product sets: high similarity/low similarity)×3 (portfolio size: small, medium and large). Results support the hypothesis about the three fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Customers who are loyal to a manufacturer's brand are less likely to become loyal with store brand (Broyles, Ross, & Davis, 2011). Liu and Hu (2011) found that the complementary products with same brand resulting in connivance and maximization of output of core the product are also the source of brand loyalty. Pricing strategies may be different for different products because of different marketing strategies.…”
Section: Brand Loyaltymentioning
confidence: 99%
“…Customers who are loyal to a manufacturer's brand are less likely to become loyal with store brand (Broyles, Ross, & Davis, 2011). Liu and Hu (2011) found that the complementary products with same brand resulting in connivance and maximization of output of core the product are also the source of brand loyalty. Pricing strategies may be different for different products because of different marketing strategies.…”
Section: Brand Loyaltymentioning
confidence: 99%
“…Hotel brand portfolio strategy same segment (Liu and Hu, 2011). Moreover, another apparent risk is the potential spillover effect of a negative image from the endorser to its endorsed brand (Erdem and Sun, 2002).…”
mentioning
confidence: 99%
“…Similarly, another study found that not all the dimensions of brand personality affect the brand loyalty; only extraversion is believed to have a significant impact on the loyalty (Lin, 2010). Liu and Hu (2011) posited that another factor which may add to the brand loyalty is the complementary products, which help enhancing the output of the core product and brand loyalty to the core brand as well. Pricing strategy also plays a certain role in the phenomenon.…”
Section: Brand Loyaltymentioning
confidence: 99%